Case studies in adapted physical education : empowering critical thinking - Hodge, Samuel R.; Murata, Nathan M.; Block, Martin E.; Lieberman, Lauren J. (b, 2020)
"Covering self-contained adapted physical education classes, general physical education programs, as well as youth sports and community recreation, this book presents a series of case studies of teaching individuals of varied ability and disability in physical activity settings. Outlining realistic scenarios, it encourages an interactive, problem-solving teaching and learning style, and the development of critical thinking skills. Now in a fully revised and updated second edition, the book covers a wide range of different professional issues, themes, disabilities and conditions, from assessment and behavior management processes to working with students with intellectual disabilities, motor difficulties, chronic illness or obesity. Each case study includes questions that challenge the reader to reflect on the practical issues involved and how to build inclusive teaching strategies. This book is valuable reading for all physical education students, teacher candidates, and novice and experienced teachers looking to deepen their understanding of adapted physical education and to improve their professional practice. It is an essential companion to any adapted physical education or physical activity course"--
Includes bibliographical references and index.
Keywords: Physical education for children with disabilities -- Case studies. -- Study and teaching